KAJIAN EFEKTIVITAS PELAKSANAAN AMDAL BIDANG ENERGI DAN SUMBER DAYA MINERAL DALAM PELESTARIAN KAWASAN LINDUNG DI KABUPATEN BENGKULU TENGAH - Meri Maya Sari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Development is a process of environmental and natural resource management for a prosperous of human life. The effort to conservation and prevent pollution or environmental damage includes planning, utilization control, maintenance, supervision and enforcement. one of the instrument is Environmental Impact Assessment (EIA). The district Middle of Bengkulu has resources of coal mining. Therefore, the production process can have an impact of environmental especially in protected area. The research was conducted at Middle of Bengkulu on January-February 2016. The purpose of this study are to identify the coal mining activities, analyze the effectiveness from EIA of energy and mine resources in conservation of protected area at Middle of Bengkulu and formulate the policies of effectiveness from EIA implementation in conserving the protected area. The research data obtained through observation, interviews, review of the literature and Geografic Information System (GIS) analysis to the change of land cover and land use. Weighting or scoring for the quality analysis of documents and the eligibility criteria. The result of analysis shows that the effectiveness of implementation of the EIA depend on attitude of companies. The EIA imlementation is two coal mining companies are still activ, showing that one of these companies has effective working aspects of obedience >90%. In the other companies can be said to be ineffective for many violations. EIA effectiveness of EMR in the conservation of protected areas can not be said to be effective, it is showed by the deteriorating condition of the river bank and Hunting Park Semidang Bukit Kabu of protected areas were damage. But the change was also influenced by industrial and domestic waste and river water quality as well as encroachers in hunting park.